Propuesta de estrategias de aprendizaje mediadas por tic, para mejorar el proceso de enseñanza- aprendizaje, en el bloque de álgebra y funciones de la asignatura de matemática del décimo grado de la Unidad Educativa “Pio Jaramillo Alvarado” de la ciudad de Loja, durante el año lectivo 2020-2021. - Abad Acaro, Vanessa Patricia (2022)
This research was developed with the purpose of supporting the teaching-learning process in the subject of mathematics, promoting the use of technological tools as they are currently a means to strengthen the contents taught, since they allow teachers to develop innovative methodologies to maintain greater interaction within the classroom. The objective was to design a proposal of strategies mediated by Information and Communication Technologies (ICT), as a support to the teacher's work in the algebra and functions block of tenth grade of General Basic Education (EGB) of the Pio Jaramillo Alvarado Educational Unit. This study was based on the quantitative approach, with a descriptive scope, since a detailed and interpretative analysis of the characteristics of the teaching-learning process was carried out; additionally, the deductive method and the statistical model were used for the review and validation of the technological tools; with respect to the research instruments, an ad hoc questionnaire was developed to apply the survey and the virtual resources were selected through technical-pedagogical cards, which were then validated by means of the LORI instrument. For the collection of information, teachers who teach the subject of mathematics in the tenth grade were taken as a sample. Among the results of the strategies mostly used by educators, interactive material, problem solving, motivation, collaborative learning and prior knowledge were identified. Regarding the choice of virtual tools, 6 were collected, but through the LORI instrument only 3 met the requirements to be validated, these are: Khan Academy, ThatQuiz and Graspable Math, according to this, the guide of methodological strategies for ICT-mediated learning was developed and incorporated. Keywords: ICT; Learning strategies; Technological tools; EGB; Mathematics.